Effect of arm swinging on lumbar spine and hip joint forces. (21st March 2018) - Angelini, Lorenza; Damm, Philipp; Zander, Thomas; Arshad, Rizwan; Di Puccio, Francesca; Schmidt, Hendrik
Abstract: During level walking, arm swing plays a key role in improving dynamic stability. In vivo investigations with a telemeterized vertebral body replacement showed that spinal loads can be affected by differences in arm positions during sitting and standing. However, little is known about how arm swing could influence the lumbar spine and hip joint forces and motions during walking. The present study aims to provide better understanding of the contribution of the upper limbs to human gait, investigating ranges of motion and joint reaction forces. A three-dimensional motion analysis was carried out via a motion capturing system on six healthy males and five patients with hip instrumented implant. Each subject performed walking with different arm swing amplitudes (small, normal, and large) and arm positions (bound to the body, and folded across the chest). The motion data were imported in a commercial musculoskeletal analysis software for kinematic and inverse dynamic investigation. The range of motion of the thorax with respect to the pelvis and of the pelvis with respect to the ground in the transversal plane were significantly associated with arm position and swing amplitude during gait. The hip external-internal rotation range of motion statistically varied only for non-dominant limb. Unlike hip joint reaction forces, predicted peak spinal loads at T12-L1 and L5-S1 showed significant differences at approximately the time of contralateral toe off and contralateral heel strike. Therefore, arm position and swing amplitude have a relevant effect on kinematic variables and spinal loads, but not on hip loads during walking.